Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3945/jn.117.257386
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Child Supplementation with Lipid-Based Nutrient Supplements, but Not Child Supplementation Alone, Decreases Self-Reported Household Food Insecurity in Some Settings

Abstract: Background: It is unknown whether self-reported measures of household food insecurity change in response to food-based nutrient supplementation.Objective: We assessed the impacts of providing lipid-based nutrient supplements (LNSs) to women during pregnancy and postpartum and/or to their children on self-reported household food insecurity in Malawi [DOSE and DYAD trial in Malawi (DYAD-M)], Ghana [DYAD trial in Ghana (DYAD-G)], and Bangladesh [Rang-Din Nutrition Study (RDNS) trial].Methods: Longitudinal househo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…We previously demonstrated that LNS-PL increased birth weight and reduced newborn stunting and that the group receiving both LNS-PL and LNS-C had improved child growth status at 18 to 24 months of age compared with the group in which the mothers received IFA and the children received MNP from 6 to 24 months (Dewey et al, 2017). We also found that daily provision of LNS during pregnancy and to children from 6 to 24 months improved household food security (Adams et al, 2017) and LNS during pregnancy increased mid-upper arm circumference among women aged 25 years or older and those with short stature . Considering the effects of LNS-PL on birth size, food insecurity, and maternal anthropometric status, it is possible that LNS-PL may also have a beneficial impact on general newborn condition and breastfeeding behaviours by directly improving newborn health or increasing maternal confidence in her ability to breastfeed.…”
mentioning
confidence: 71%
“…We previously demonstrated that LNS-PL increased birth weight and reduced newborn stunting and that the group receiving both LNS-PL and LNS-C had improved child growth status at 18 to 24 months of age compared with the group in which the mothers received IFA and the children received MNP from 6 to 24 months (Dewey et al, 2017). We also found that daily provision of LNS during pregnancy and to children from 6 to 24 months improved household food security (Adams et al, 2017) and LNS during pregnancy increased mid-upper arm circumference among women aged 25 years or older and those with short stature . Considering the effects of LNS-PL on birth size, food insecurity, and maternal anthropometric status, it is possible that LNS-PL may also have a beneficial impact on general newborn condition and breastfeeding behaviours by directly improving newborn health or increasing maternal confidence in her ability to breastfeed.…”
mentioning
confidence: 71%
“…Poor dietary diversity has been shown to be related to the magnitude of aflatoxin exposure and increasing dietary diversity is a valuable strategy for reducing exposure to aflatoxins ( 4 ). Thus, whether strategies focus on increasing dietary diversity or on reducing household food insecurity—such as by provision of LNSs ( 58 )—a diminished dietary reliance on maize is likely to reduce aflatoxin exposure in Malawi.…”
Section: Discussionmentioning
confidence: 99%
“…Both women and children diagnosed with severe or moderate malnutrition have positive outcomes when provided Ready to Use Therapeutic or Supplemental Foods (RUTF and RUSF, respectively) as part of their therapeutic care [8,12,24,39,40]. Studies surrounding such small quantity lipid based nutritional supplements (LNS) were the focus of the International Lipid-Based Nutrient Supplements Project (iLiNS), which sought to evaluate a wide variety of impacts using various formulations of small quantity LNS (i.e.…”
Section: Discussionmentioning
confidence: 99%